VERTICO II: How H i-identified Environmental Mechanisms Affect the Molecular Gas in Cluster Galaxies - Nikki Zabel; Toby Brown; Christine D. Wilson; Timothy A. Davis; Luca Cortese; Laura C. Parker; Alessandro Boselli; Barbara Catinella; Ryan Chown; Aeree Chung; Tirna Deb; Sara L. Ellison; et al. (The Astrophysical Journal, 2022)
In this VERTICO early science paper we explore in detail how environmental mechanisms, identified in H i , affect the resolved properties of molecular gas reservoirs in cluster galaxies. The molecular gas is probed using ALMA ACA (+TP) observations of ^12 CO(2–1) in 51 spiral galaxies in the Virgo cluster (of which 49 are detected), all of which are included in the VIVA H i survey. The sample spans a stellar mass range of $9\leqslant log\,M_{\star }/M_{\odot }\leqslant 11$ . We study molecular gas radial profiles, isodensity radii, and surface densities as a function of galaxy H i deficiency and morphology. There is a weak correlation between global H i and H _2 deficiencies, and resolved properties of molecular gas correlate with H i deficiency: galaxies that have large H i deficiencies have relatively steep and truncated molecular gas radial profiles, which is due to the removal of low-surface-density molecular gas on the outskirts. Therefore, while the environmental mechanisms observed in H i also affect molecular gas reservoirs, there is only a moderate reduction of the total amount of molecular gas.